2012
DOI: 10.4028/www.scientific.net/amr.610-613.577
|View full text |Cite
|
Sign up to set email alerts
|

BaO-Modified Pd-Based Catalyst for Methanol Oxidation

Abstract: Pd-based catalysts modified with BaO as a promoter was prepared by impregnation method. The catalyst was characterized by H2-temperature-programmed reduction (H2-TPR) and X-ray photoelectron spectroscopy (XPS). The catalytic activity towards methanol showed that the BaO modification promoted the conversion of methanol. The light-off temperature (T50), complete conversion temperature (T90) and ΔT (T90-T50) for methanol oxidation are 100°C, 125°C and 25°C, respectively. The H2-TPR results showed that the additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…In addition, peak ε for Pd 1 /Al 3 BaO shifted to a lower temperature, indicating that the doped Ba weakened the interaction between PdO x Cl y and the support. These phenomena suggested that the introduction of barium on Pd 1 /Al 3 BaO improved the dispersion of Pd and weakened the interaction of PdO species with the support, which were consistent with the CO chemisorption and TEM results and the previous report. , CO chemisorption, TEM, and H 2 -TPR results confirmed that Al 2 O 3 support modified by Ba could enhance the dispersion of Pd nanocrystals, which could facilitate the dehydrogenative aromatization of the Schiff base formed by cyclohexanone and aniline. This might be the main reasons that the Pd 1 /Al 3 BaO catalyst showed excellent activity in the reaction.…”
Section: Results and Discussionsupporting
confidence: 90%
“…In addition, peak ε for Pd 1 /Al 3 BaO shifted to a lower temperature, indicating that the doped Ba weakened the interaction between PdO x Cl y and the support. These phenomena suggested that the introduction of barium on Pd 1 /Al 3 BaO improved the dispersion of Pd and weakened the interaction of PdO species with the support, which were consistent with the CO chemisorption and TEM results and the previous report. , CO chemisorption, TEM, and H 2 -TPR results confirmed that Al 2 O 3 support modified by Ba could enhance the dispersion of Pd nanocrystals, which could facilitate the dehydrogenative aromatization of the Schiff base formed by cyclohexanone and aniline. This might be the main reasons that the Pd 1 /Al 3 BaO catalyst showed excellent activity in the reaction.…”
Section: Results and Discussionsupporting
confidence: 90%
“…This study proposed the use of bimetallic oxide with barium (Ba) precursor as a dopant to enhance the catalytic activity of Al 2 O 3 based on synergistic effects. This proposal was also based on barium oxide (BaO)-modified Pd-based catalyst that promoted methanol conversion [22]. BaO is also a promoter of La 1.6 Ba 0.4 NiO 4 catalysts that improve the catalytic activity of NO direct decomposition [23].…”
Section: Introductionmentioning
confidence: 99%